Televisão, adolescência e necropolítica: o caso do programa policialesco Cidade 190 - Silva, Calebe Rodrigues da (2024)
The paper aims to analyze the relationship between television, adolescence, and necropolitics, based on Achille Mbembe's concept of necropolitics (2018), in dialogue with Raúl Zaffaroni's concept of media criminology (2012). It seeks to understand how the police program “Cidade 190”, broadcasted by TV Cidade, an affiliate of Record in Ceará, helps to construct representations that contribute to the legitimization of political actions that promote exclusions and, ultimately, determine who can remain alive or must die. A total of 298 contents from the program “Cidade 190” were analyzed in the years 2018, 2021, and 2023, in order to perceive the recurrence of the approach to adolescents associated with criminal acts. The chosen temporal scope refers to the week marking another year since the “Chacina do Curió”, a series of homicides that occurred in the early hours between November 11 and 12, 2015, in Fortaleza, perpetrated by military police officers, resulting in the death of eleven people, including seven adolescents. The emphasis on this social group is due to the high mortality rate of black and peripheral adolescents in Ceará. Through the analysis of addressing modes, a methodology proposed by Itania Gomes (2005), it was possible to observe the construction of sensationalist and racist representations, playing an active role in legitimizing and perpetuating necropolitics concerning the social group.